Tren topik dan indeksasi artikel arsip pada Science and Technology Index (SINTA) - Restu, Rifiani Aulia; Sudiar, Nining; Amalia, Vita (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2025)
Purpose. This study aims to determine the topic trends and indexation of archival articles on the Science and Technology Index (SINTA) from 2020 to 2024. Methodology. The research method used in this study is quantitative descriptive with search on the SINTA platform and data analysis using web voyant tools. Results and discussion. The results of the study show that in the last five years, there have been 290 archive articles with a total of 1,420 keywords. The trend of topics seen by keywords is dominated by the keywords